Optical and emission properties of terpolymer active materials for white OLEDs (WOLEDs). (2021) - Gioti, M.; Papadopoulos, K.; Kyriazopoulos, V.; Kassavetis, S.; Andreopoulou, A.K.; Kallitsis, J.K.; Laskarakis, A.; Logothetidis, S.
Abstract: White Organic Light-Emitting Diodes (WOLEDs) have attracted an enormous interest because they can be implemented in numerous lighting applications as next-generation light sources. In this work, terpolymers bearing blue, yellow and red chromophores are used for the fabrication of WOLED devices. These systems provide easy tuning of white color by changing weight ratios between the chromophores. The optical and opto-electronic characterization is carried out by near infrared–visible-far ultraviolet (NIR–Vis–FUV) Spectroscopic Ellipsometry (SE), Photoluminescence (PL), and Electroluminescence (EL), whereas the structural characterization is achieved by Atomic Force Microscopy (AFM), to provide valuable information toward the optimization and functionalization of these WOLED devices.